(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The all-encompassing image of Shri Ram and his literary value stand as a synonym for one another in Gujarati poetry. The story of Ramayana has occupied an important place in the hearts of the Indian people for centuries. Ram is still worshipped as a dutiful king and a man of virtue.